Pathotypes and Phenotypic Resistance to Antimicrobials of Escherichia coli Isolates from One-Day-Old Chickens - Katerina Nedbalcova; Jaroslav Bzdil; Aneta Papouskova; Monika Zouharova; Katarina Matiaskova; Kamil Stastny; Vladimir Sladecek; David Senk; Matej Petr; Petr Stolar (Pathogens, 2023)
The aim of this work was to describe the pathotypes of Escherichia coli strains isolated from one-day-old chickens, as well as the occurrence of resistance and multidrug resistance (MDR) in these strains. A total of 429 mixed swabs from 4290 one-day-old chicks were examined between August 2021 and July 2023 (24 months) during routine point-of-destination inspections at 12 poultry farms in the Czech Republic. All samples were processed via cultivation methods using meat-peptone blood agar and Mc Conkey agar under aerobic conditions at 37 ± 1 °C for 18–24 h. The identification of the strains was performed using MALDI-TOF mass spectrometry. All confirmed strains of E. coli were screened via single or multiplex PCRs for the presence of genes encoding the virulence-associated factors iroN, cvaC, iss, felA, iutA, frz and tsh. Antimicrobial susceptibility tests were performed using the minimal inhibitory concentration (MIC) method, focusing on ampicillin, cefotaxime, tetracycline, doxycycline, enrofloxacin, florfenicol, amoxicillin with clavulanic acid and trimethoprim with sulfamethoxazole. A total of 321 E. coli strains (prevalence of 74.8%) were isolated, and 300 isolates were defined as avian pathogenic strains of E. coli (APEC) via multiplex PCR. Based on the defined virulence genes, the isolates were classified into 31 pathotypes. A total of 15.9% of the tested isolates were susceptible to all the tested antimicrobials. On the other hand, 20.5% of the isolates were identified as multidrug-resistant (8.7% of isolates were resistant to three antimicrobials, 7.3% to four antimicrobials, 3.6% to five antimicrobials and 0.9% to six antimicrobials). Monitoring pathogenic strains of E. coli in different animals and in the environment makes it possible to understand their spread in animal and human populations and, at the same time, reveal the sources of virulence and resistance genes.